Investigation of the proactive personal traits of faculty of sports sciences students and their status of the psychological needs in sports - Volkan Sural; Bekir Car; Ali Erdogan; Erkan Faruk Sirin (ROL Spor Bilimleri Dergisi)
The aim of this study was to examine the proactive personality and psychological needs in sport of the students studying at the faculty of sport sciences according to the various and to determine whether there is a relationship between proactive personality and psychological needs in sport. The research was conducted according to the survey model from quantitative approaches. 315 students studying at Karamanoğlu Mehmetbey University, Faculty of Sport Sciences participated in the study voluntarily. Psychological Need Status in Sport Scale, Proactive Personality Scale and personal information form created by the researchers were used in the study. Non-parametric tests were used to analyze the data. According to the findings, a significant difference was found in favor of female students in the autonomy satisfaction and proactive personality scale, and in favor of male students in the belonging dissatisfaction sub-dimension. Also, there was a significant difference in favor of students between the ages of 18-21 in the autonomy satisfaction sub-factor, and in favor of students aged 22 and over in the belonging dissatisfaction sub-dimension. In addition, it was found that students interested in individual sports had higher autonomy satisfaction than students interested in team sports. The scores related to both scales and sub-factors did not differ in terms of the variables of the department and the year of sport. Finally, there was a positive and significant relationship between the psychological need status in sport and proactive personalities of the students of the faculty of sport sciences.